[Afisz. Incipit] Niech żyje Święto Ludowe 16.V.1948 ... (Kościerzyna : [wydawca nieznany], 1948)
Afisz informujacy o święcie w Kościerzynie.
Keywords: Kościerzyna (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.